Laryngopharyngeal reflux in war-torn Syria and its association with smoking and other risks: an online cross-sectional population study - Ameer Kakaje; Mohammad Marwan Alhalabi; Ayham Alyousbashi; Aya Hamid; Yousef Mahmoud (BMJ Open)
Objectives To demonstrate the burden of laryngopharyngeal reflux (LPR) in Syria and its associated variables.Design This is a cross-sectional study that used online questionnaires that included demographics, smoking, war-related questions and reflux symptom index (RSI).Setting This research was conducted online across Syria and included the general population.Participants Participants who lived in Syria, agreed to participate, and responded to all the RSI questions were included. This research comprised 734 participants, with 94.6% response rate, 75.5% being females, and a mean age of 24 years.Results Overall, 31.9% of subjects had symptoms suggestive of LPR. Participants who were 30 years and younger had fewer symptoms suggestive of LPR compared with the older group p=0.012 (OR 0.534; 95% CI 0.325 to 0.877). While having an epigastric burning sensation, chest pain and indigestion were the most common symptoms, having a sore throat was the least common. Being distressed from war noises was associated with more symptoms p=0.009 (OR 1.562; 95% CI 1.117 to 2.183). However, losing someone or changing place of living due to war were not significantly associated with these symptoms p>0.05. RSI scores were associated with cigarette and/or shisha smoking p<0.05. Finally, asthma, allergic disorders and having a job were associated with having LPR symptoms p<0.05. No significant findings were observed in consanguinity, marital status, educational level and socioeconomic status.Conclusions War, smoking, asthma, allergies, respiratory conditions and having a job were associated with LPR symptoms. However, they may be associated with these symptoms independently from LPR; for instance, similar symptoms can be caused by the mental disorders from war, the unique environment and irritant substances of the laryngeal mucosa.